KREATIVITAS GURU IPS DI MASA PANDEMI COVID -19 DALAM MENINGKATKAN MOTIVASI BELAJAR SISWAKELAS VII DI SMP NEGERI 21 MAKASSAR - Rusnipati Lis Angriani; Nurdin . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to determine the teaching and learning process of teachers Social Studies with students during the civid -19 pandemic. The data collection techniques used used are observations, interviews and documentation. The data analysis technique is carried out by analyzing the research results based on data reduction, data presentation and drawing conclusions. The results showed that: (1). Teaching and learning process Social studies teacher with students during the Covid-19 pandemic, class VII in junior high school State 21 Makassar, namely: a). Implementing distance learning (PJJ) online, b). Implement limited face-to-face learning (PTMT). (2). The creativity of social studies teachers during the covid-19 pandemic in improving the learning motivation of class VII students at SMP Negeri 21 Makassar, namely: a). Prepare lesson plans in social studies lessons, b). Using learning media which more varies in social studies lessons, c). Rewarding effort and achievements made by students in the social studies learning process.  Keywords: Social studies teacher creativity, learning motivation